Think positive: Proposal of a simple method to create reference materials in the frame of microplastics research - Alexandre Dehaut; Charlotte Himber; Mathilde Colin; Guillaume Duflos (MethodsX, 2023)
In the context of the harmonization of methodologies employed to isolate and count microplastics in samples or to organize ring trials tests, the use of reference materials, i.e. samples with controlled amount of particles is required. The method proposed here uses transparent, sealed capsules containing in-house generated microplastics as a convenient way to generate microplastic reference materials. This method is a simple approach for adding particles to samples without risk of loss during particle extraction or transporting/handling. • Low-cost and easy-to-use preparation of heterogeneous mix of microplastic reference particles • Possibility to control microplastic size, shape, and polymeric composition • Applicable to many protocols and wide range of applications on water, sediments and biota.